Long-term changes in the snow-firn pack stratigraphy on Urumqi glacier No. 1, Eastern Tien Shan, China - Wang, F.; Li, Z.; Edwards, Peter; Li, H. (International Glaciological Society, 2007)
We report on changes to the snowpack of Ürümqi glacier No. 1, eastern Tien Shan, China, resulting from climate change between 1961 and 2005. Data from more than 120 snow pits were used to investigate temporal changes in the snow stratigraphy for three periods 1961–62, 1980–83 and 2002–05. Both the thickness and structure of the snow were found to be significantly altered by climatic warming. The proportion of coarse-grained firn, which is usually formed by infiltration water, was found to have increased from 40% to 65% over the period 1961–2005, and the distribution of the glacier zones also changed significantly, with all boundaries moving up-slope. The recrystallization–infiltration zone disappeared in 1989. The mean ablation rate over the melt season increased by ~26% from 1962 to 1980 at the west branch site and by ~75% from 1980 to 2004 at the east branch site.